ANITA CANAVARRO: BLACKING CHEMISTRY - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
The teacher Anna Mª Canavarro Benite is Doctor and Master of Science and a degree in Chemistry from the Federal University of Rio de Janeiro. Coordinator of the Research Laboratory in Chemical Education and Inclusion (LPEQI) and Coletivo Negro Ciata, of the Chemistry Institute of the Federal University of Goiás. In addition, she is the creator of the Investiga Menina Project, which seeks to inspire black students to pursue careers in the exact and scientific.